Sustainable Materials for Tribological Applications - Mohan A.; Gautam G.; Kumar N.; Mohan S. (My University, 2025)
Chapter starts with the future challenges for the tribologists and provides an understanding of the deliverables of composites as sustainable materials while comparing with respective matrices. Examples there-off clearly distinguish the superiority of composites in ultimate tensile strength, yield strength and hardness. Even ductility can also be improved with proper combination of matrix and reinforcement or morphology alteration. It is also seen that combination of wear and friction can also be altered as per need. Different sections deal with the number of important applications on the basis of industry, environment, and composite used. © 2020 Elsevier Inc. All rights reserved